The principal (P) is $6000 and the interest rate (r) is 0.02.
Now if the loan was for 1 month we would have
`L=P(1+r)` or `P=L/(1+r)`
If the loan was for 2 months we would have
`(1+r)((1+r)P-L)=L` or `(1+r)^2P-(1+r)L=L` which gives `P=L/(1+r)+L/(1+r)^2`
So if the loan is n months we would have
`P = sum_(j=1)^n L/(1+r)^j=L sum_(j=1)^n 1/(1+r)^n`
We can solve this by noting that
`(1+r)P=L sum_(j=0)^(n-1) 1/(1+r)^n`
`(1+r)P - P = rP = L(1-1/(1+r)^n)`
Substituting P = $6000, r = 0.02 and n = 24
`L = (0.02(6000))/(1-1/(1-0.02)^24)`
Evaluating we get $317.23 per month. Now this does seem high since 6000/24=250 but 2% per month is 48% for the entire loan, so this is actually a high interest rate made more attractive by stating it as a monthly interest rate.
So the final answer is $317.23 will pay off the loan in 24 months.